2020
DOI: 10.1109/access.2020.3026539
|View full text |Cite
|
Sign up to set email alerts
|

Signal Separation Using a Mathematical Model of Physiological Signals for the Measurement of Heart Pulse Wave Propagation With Array Radar

Abstract: The arterial pulse wave, which propagates along the artery, is an important indicator of various cardiovascular diseases. By measuring the displacement at multiple parts of the human body, pulse wave velocity can be estimated from the pulse transit time. This paper proposes a technique for signal separation using an antenna array, so that pulse wave propagation can be measured in a non-contact manner. The body displacements due to the pulse wave at different body parts are highly correlated, and cannot be accu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…(2) The user is required to hold their breath for a few seconds during the measurement process. To mitigate the first disadvantage, we will study application of advanced signal processing techniques [35] to improve the signal separation accuracy. To resolve the second disadvantage, it will be necessary to develop an algorithm that can suppress the respiratory components from the radar signals, and this will form part of our future studies.…”
Section: B Advantage and Disadvantage Of The Proposed Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) The user is required to hold their breath for a few seconds during the measurement process. To mitigate the first disadvantage, we will study application of advanced signal processing techniques [35] to improve the signal separation accuracy. To resolve the second disadvantage, it will be necessary to develop an algorithm that can suppress the respiratory components from the radar signals, and this will form part of our future studies.…”
Section: B Advantage and Disadvantage Of The Proposed Approachmentioning
confidence: 99%
“…The pulse wave propagation channel is evaluated quantitatively in terms of its impulse response, which is calculated based on the estimated displacement waveforms from the two body parts. Although our previous study [35] indicated the possibility of array-radar-based pulse wave propagation measurement, the accuracy of these measurements has not been evaluated experimentally to date. To the extent of the authors' knowledge, this study is the first to evaluate the accuracy of radar-based noncontact measurements of arterial pulse wave propagation quantitatively.…”
Section: Introductionmentioning
confidence: 99%
“…These techniques that use an array radar system require accurate signal separation so that tiny displacements at multiple body parts are estimated accurately. To improve the signal separation accuracy, [12] introduced an algorithm based on optimization with a mathematical model of physiological signals. This technique is called physiological component analysis (PHCA) and has achieved high accuracy in separating signals when the echoes are modulated by constant multiples of time-shifted displacement waveforms.…”
Section: Ieice Communications Express Vol 1-6mentioning
confidence: 99%
“…We proposed PHCA [12] to determine an N ×M matrix W = [w 1 w 2 • • • w N ] T and estimate echoes asŝ(t) = W x(t), which leads to the estimate of the displacementd(t) = (1/2k)∠ŝ(t), where ∠ denotes the argument of a complex number. Note that ambiguity is allowed in the permutation and constant multiplication when we estimated(t).…”
Section: Physiological Component Analysismentioning
confidence: 99%
See 1 more Smart Citation